On the transcendence of some power series - Gozeri, Gul Karadeniz; Pekin, Ayten; Kilicman, Adem (Springer, 2013)
In this study, we consider some power series with rational coefficients and investigate transcendence of the values of these series for Liouville number arguments. It is proved that these values are either a Liouville number or a rational number under certain conditions.